DIGITAL TECHNOLOGY CONTRIBUTIONS IN ACTUALIZING DAWUHAN AS AN INTERNATIONAL TOURISM VILLAGE - Savitri, Dhian Andanarini M; Taswan; Salim, Noor; Bhandari, Rahul; Ratsameemothon, Chadchom; Nasir, Wan Mohd Nazdrol bin Wan Mohd; Mariska, Azza; Aulia, Fiqhi (Perwira Journal of Community Development, 2023)
Dawuhan Village, located in Banjarnegara district, has a very high potential in terms of MSME potential and tourism village potential. The Tourism Village in Dawuhan village has led to an International Tourism Village where many foreign tourists have dated. The attraction of Dawuhan Tourism Village lies in the existence of the Rengrang Market which is professionally managed but presents a thick village atmosphere. Rengrang Market is also a potential market for MSME actors to trade their MSME products. The limitation that still needs to be improved in the management of Dawuhan Tourism Village is the ability of its human resources to utilize digital technology. For this reason, it is necessary to conduct training and assistance regarding digital marketing, digital financial reports, good tourism management, photo-making training, and E-catalogs. The training and mentoring carried out succeeded in increasing participants' knowledge about marketing digitalization and changes in the improvement of tourism magazines. Another positive impact that can be seen is that MSME participants and Dawuhan Tourism Village have begun to record financial statements properly and separately from household finances.